If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + -5) = 32 Reorder the terms: 2(-5 + 3x) = 32 (-5 * 2 + 3x * 2) = 32 (-10 + 6x) = 32 Solving -10 + 6x = 32 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 6x = 32 + 10 Combine like terms: -10 + 10 = 0 0 + 6x = 32 + 10 6x = 32 + 10 Combine like terms: 32 + 10 = 42 6x = 42 Divide each side by '6'. x = 7 Simplifying x = 7
| 2y+5=6y+26 | | x^2-25=75 | | 0.4(x-3)=1 | | 80=x*0.75 | | 4=s-3 | | 6x+.2x=24.8 | | -4m^2-35m=0 | | 10=y | | 10y-15=9y | | -11-10x=10x+23 | | 2[(5w+3)-(w+1)]=3(1+w) | | 2(4x+1)+2(2x-3)=220 | | 60-5w=135-10w | | 2(7x-4)+8x=124 | | 5g-25=10 | | 3x^2+6x+3=27 | | log(9x+7)=2 | | -11-5=10-8x | | 12x^4-7x^2=0 | | 3x^2+19x=28 | | 3x+1=-1 | | -4[2(x-7)+3]+20= | | 2n=0.5+30 | | r-(-3)=3 | | 4x-2-2x=6x-4 | | 4x^2+17x=15 | | r+3=3 | | r-6=-13 | | 3x-9/4=6 | | 4-r=1 | | 12(2x-1)/6=24 | | f+9=6 |